The Effect of Post-Purchase Perceived-Value towards the Relationship Quality of Hajj and Umrah Travel Agencies in Indonesia - Oktora, Kiki; Achyar, Adrian (UI Scholars Hub, 2014)
One out of four people in the world is a Moslem, and Indonesia ranks first on the biggest Moslem population in the world. Hundreds of thousands of people go to Makkah each year to make Hajj (pilgrimage). Hajj and Umrah travel agencies as providers of Hajj and Umrah packages are becoming important in Indonesia, as their number is about two hundred agencies. However, there has been little discussion about Hajj and Umrah, especially on Hajj and Umrah travel agencies. The purpose of this paper is to identify the relationships of post-purchase perceived-value to relationship quality, which consists of satisfaction, commitment, and trust, on Hajj and Umrah travel agencies. This study finds that the post-purchase perceived-value significantly affects satisfaction and trust but does not affect commitment. Moreover, satisfaction significantly affects trust and commitment, while trust does not affect commitment.